Managing Human Tissue Transfer Across National Boundaries – An Approach from an Institution in South Africa. Issue 1 (17th February 2015) - Mahomed, Safia; Behrens, Kevin; Slabbert, Melodie; Sanne, Ian
Abstract: With biobank research on the increase and the history of exploitation in Africa, it has become necessary to manage the transfer of human tissues across national boundaries. There are many accepted templates of Material Transfer Agreements (MTAs) that currently exist internationally. However, these templates do not address the specific concerns of South Africa and even of Africa as a continent. This article will examine three significantly important ethico‐legal concepts that were deliberated and carefully adapted by a South African Institution to suit the transfer of Human Biological Materials (HBMs) and associated data for biobank research, namely: informed consent; benefit sharing arrangements; and ownership together with intellectual property rights in human tissues. The discussion includes an analysis of current practice; the ethico‐legal challenges in the South African/African context; the decisions made with regard to how the related ethico‐legal challenges were addressed in the MTA; and justifications for implementing these decisions. The processes considered could be of benefit to other developing world countries who consider it necessary to manage the transfer of HBMs across national boundaries.